»Žitje protopopa Avvakuma« Ruska tradicija na preizkušnji - Zajc, Neža (Življenja in dela, 2009)
Through the analysis of the Old Russian mentality in the seventeenth century, the monograph ('"The Life of Archpriest Avvakum" : Russian Tradition Put to the Test') sheds light on the problem and cultural-historical specificity of the phenomenon of the so-called Old Russian literature. Linguistic complexities (prohibitions, rules) point to deep-rooted norms that prescribed the Old Russian way of governing, the ecclesiastical system and the relationship between dealing with the existing knowledge and Christian tradition.